If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + 147 = 180 Reorder the terms: 147 + 3u = 180 Solving 147 + 3u = 180 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-147' to each side of the equation. 147 + -147 + 3u = 180 + -147 Combine like terms: 147 + -147 = 0 0 + 3u = 180 + -147 3u = 180 + -147 Combine like terms: 180 + -147 = 33 3u = 33 Divide each side by '3'. u = 11 Simplifying u = 11
| x(x+1)=1024 | | x=15+7x-81 | | -7+3+-5= | | 6x-19=10x-79 | | 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= | | x^2+X(c-b)+(c-a)(a-b)=0 | | 4x-90=3x-60 | | 5x+3y=56 | | abc-cba=973 | | -9x+1=-26 | | abc-cba=891 | | 4*sinx*cosx+2*cosx+1=0 | | abc-cba=675 | | 3a+7+2a=18-9 | | abc-cba=456 | | 15z-75=180 | | x-11=4x+44 | | 6(x-3)=2(3x-5) | | 4t-66=5t-87 | | sin(2x)+2*cosx+1=0 | | X^4-x^3-27x^2+25x+50=0 | | 4(5x-3)=2x-34 | | 8q-67=6q-35 | | 3(c+5)=2(c+3)-11 |